REVISITING THE MECHANISMS OF FUNCTIONING OF THE ARTISTIC SPACE OF AN OLD EGYPTIAN PRIVATE TOMB - Fedor I. Kulikov (Russian Studies in Culture and Society, 2023)
This paper examines the mechanism of functioning of the artistic space of the Egyptian noble tomb of the Old Kingdom period as a system of pictorial and architectural components. The purpose of the burial and the mechanism of functioning of the system to a great extent determined the themes and content of the plots, which contributes a special relevance to the study. A systematic analysis of reliefs from more than a hundred burials of the necropolises of Giza and Saqqara is used, with a focus on the design of the large tombs of Yasen and Chi. The paper emphasizes the fact that the universal mechanism for the functioning of the level system “a large image of the owner – a nearby scene” is a stable correlation between the elements of the attribute set of the nobleman and the content of the plots. Moreover, a large image of the nobleman is valuable not only as an image itself, but also as a set of necessary attributes that allow one to engage in “contemplating” on the images corresponding to these attributes. A new unusual variant of correlation has been identified by depicting a nobleman without the required attribute, however in a certain pose in which this attribute is usually present. Thus, the combination of the necessary insignia, combined with the pose of the depicted nobleman, endowed the large image of the owner with additional functions, allowing it to correlate with several plots and scenes of different content.